Philosophy, politics, and Austrian economics - D'Amico, Daniel J.; Martin, Adam G. (Emerald Publishing Limited, 2020)
Philosophy, Politics, and Economics (PPE), as an interdisciplinary endeavour, has surged in popularity in recent years. Work in this field usually draws on standard microeconomics to grapple with questions from political philosophy. But what might Austrian economics, which offers an alternative approach to economic theory, have to offer to this endeavour? Featuring contributions by economists, philosophers, political scientists, and political theorists both friendly to and critical of Austrian ideas, this collection explores what, if anything, Austrian assumptions about human nature and the function of social institutions have to offer the broader field of PPE. The authors explore the relationship of F.A. Hayek's thought to contemporary analysis of democracy, the importance of entrepreneurship for institutional analysis, the possibility and perils of self-governance, and whether Austrian ideas can better explain real-world institutional developments.
Includes index.
Keywords: Austrian school of economics.; Political science -- Philosophy.; Business & Economics -- Economics -- Theory.; Economic theory & philosophy.; elektronické knihy; electronic books